Level of associativity of the entrepreneurial sector of the popular and solidary economy, Machala canton - Santana Ochoa, Karen Yamileth; León-Serrano, Lady Andrea (Cooperativismo & Desarrollo, 2021)
In order to improve the functioning of the organizations of the popular and solidary economy of the Machala canton, it is proposed to determine their level of associativity and discuss some forms of incentive for their members. Then, an estimated weighting of each characteristic of this informal business sector is achieved. With this purpose, a series of indicators are proposed that allow organizations to be classified according to their characteristics, management model and contribution to economic and social development. Established the fundamental parameters of the entrepreneurial sector of the popular and solidarity economy, those intervals that are applicable to compare the degree of association of the different organizations of the Machala canton are estimated. It is established that decision-making is the main indicator of solidarity association, followed by factors of production and the distribution of surpluses. The relative low associativity of the popular and solidarity economy organizations of the Machala canton makes it urgently necessary to promote training, inclusion and accompaniment policies.